The alleged endemic yellow fever on the coast of Peru (Continued) - Arce, Julián (1919)
So far, we have only had to study and discuss certain isolated cases have been wrongly categorized amarílicos which have occurred outside the epidemic periods 1852-1856 and 1867-1869, asignándoseles, in that case, the probative value of endemicity yellow fever in the Peruvian coast, a view which, as we have seen, is wholly unfounded. . This statement, moreover, is not only our, because in 1885 Drs JOSE MARIANO Macedo and Leonardo Villar, referring to such cases, say the following: "Sporadic cases of fever, reputed by some to be practical typhus icterodes that have occurred in the interim periods between epidemics and another, can not be referred to these, or be subject to them of course, these cases are not typically well-defined and proven by autopsy, and nor ever have been transmissible. "I must do this, that this categorical statement also includes, of course, the case of yellow fever by reputed VILLAR 1864.